Effects of Diamond Nanoparticles on Rubber Compounds - Mohammadmahdi Kamyabi; Seyed Mohammad Sadegh Hosseini; Hanieh Jamalizadeh (Baspārish, 2022)
In the last few decades, various polymer industries have witnessed the increasing use of nanoparticles for various applications. Rubber industry is one of these industries and nanodiamond is one of these nanoparticles. Nanodiamond has received special attention in various industries due to its outstanding properties such as excellent mechanical properties and high thermal conductivity. For example, the use of nanodiamond in rubber compounds alone or in combination with other fillers has recently received a lot of attention. By combining these nanoparticles with rubber matrix, different types of rubbers with more capabilities have been produced. These capabilities include better physical, mechanical and thermal properties as well as easier curing procedures. The mentioned properties are mostly due to the active surface of the nanodiamond as well as its excellent thermal conductivity. In general, nanodiamonds are used in the rubber industry for different purposes. In this article, while introducing these reasons and purposes, the use cases of this nanoparticle in various types of rubber such as natural rubber, styrene-butadiene, nitrile, etc. have been discussed.  The latest research in this field has been reviewed and the final results have been presented in summary.